Single-stage Matriderm and skin grafting as an alternative reconstruction in high-voltage injuries - Ryssel, Henning; Radu, Christian Andreas; Germann, Günter; Otte, Maximilian; Gazyakan, Emre (International wound journal, 2010)
This article presents a retrospective analysis of a series of nine patients requiring reconstruction of exposed bone, tendons or joint capsules as a result of acute high-voltage injuries in a single burn centre. As an alternative to free tissue transfer, the dermal substitute Matriderm® was used in a one-stage procedure in combination with split-thickness skin grafts (STSG) for reconstruction. Nine patients, in the period between 2005 and 2009 with extensive high-voltage injuries to one or more extremities which required coverage of exposed functional structures as bone, tendons or joint capsule, were included. A total of 11 skin graftings and 2 local flaps were performed. Data including regrafting rate, complications, hospital stays, length of rehabilitation and time until return to work were collected. Eleven STSG in combination with Matriderm® were performed on nine patients (success rate 89%). One patient died. One patient needed a free-flap coverage as a secondary procedure. The median follow-up was 30 months (range 6-48 months). The clinical results of these nine treated patients concerning skin-quality and coverage of exposed tendons or joint capsule were very good. In high-voltage injuries free-flap failure occurs between 10% and 30% if performed within the first 4-6 weeks after trauma. The use of single-stage Matriderm® and skin grafting for immediate coverage described in this article is a reliable alternative to selected cases within this period.